2022
DOI: 10.1038/s41467-022-29227-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of PTEN mutational profile in a series of 34,129 colorectal cancers

Abstract: Loss of expression or activity of the tumor suppressor PTEN acts similarly to an activating mutation in the oncogene PIK3CA in elevating intracellular levels of phosphatidylinositol (3,4,5)-trisphosphate (PIP3), inducing signaling by AKT and other pro-tumorigenic signaling proteins. Here, we analyze sequence data for 34,129 colorectal cancer (CRC) patients, capturing 3,434 PTEN mutations. We identify specific patterns of PTEN mutation associated with microsatellite stability/instability (MSS/MSI), tumor mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 98 publications
(131 reference statements)
3
9
0
Order By: Relevance
“…Functional activities associated with immune response included regulation of granulocyte-macrophage colony-stimulating factor production, neutrophil migration, and regulation of leukocyte-mediated cytotoxicity. These findings are consistent with recent studies that showed that PTEN mutation was associated with microsatellite stability/instability and tumor mutational burden in colon cancer 48 . Both in vitro studies 49 and recent analyses of colon tumors 50 suggest that PTEN loss in colorectal carcinoma may activation of PI3K and upregulate PD-L1 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Functional activities associated with immune response included regulation of granulocyte-macrophage colony-stimulating factor production, neutrophil migration, and regulation of leukocyte-mediated cytotoxicity. These findings are consistent with recent studies that showed that PTEN mutation was associated with microsatellite stability/instability and tumor mutational burden in colon cancer 48 . Both in vitro studies 49 and recent analyses of colon tumors 50 suggest that PTEN loss in colorectal carcinoma may activation of PI3K and upregulate PD-L1 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Pt#2 with a POLE candidate PGV also harbored candidate PGVs in BRCA2, PDGFRA. In other studies, hypermutant ccRCCs also carried mutations in TP53, PTEN, VHL, and UNC5C (45,46). It is also possible that defects in polymerase genes affect cancer risk by affecting biological processes beyond DNA replication and repair.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, different types of mutations and dosages of PTEN result in different diseases: heterozygous loss-of-function of PTEN has been associated with ASD (Busch et al, Transl Psychiatry, 2019; Butler et al, J Med Genet, 2005; Frazier et al, Mol Psychiatry, 2015, Serebriiskii et al, 2022), while both heterozygous and homozygous PTEN loss-of-function has been associated with tumor syndromes (Krohn et al, Am J Pathol, 2012; Wang et al, Clin Cancer Res, 1998). We therefore investigated whether different dosages of PTEN may result in different phenotypes also in brain organoids.…”
Section: Main Textmentioning
confidence: 99%